Unregistered and Online Marriage in Indonesia: An Islamic Law and Legal Perspective Based on the Principle of Al-Masyaqqah Tajlibu al-Taysīr - Yusuf Agung Purnama; Slamet Firdaus; Wahyudi Wahyudi; Maryna Chernysh; Achmad Siddiq (Universitas Muhammadiyah Bandung, 2026)
Marriage in Islam is a sacred contract that has a worship and social dimension, so its regulation is a concern in Islamic law and state law. Social and technological developments have given birth to contemporary marriage practices such as serial marriage and online marriage contracts that raise legal issues, especially related to the validity and legal protection for women and children. This study aims to analyze these two practices in the perspective of Islamic law and positive Indonesian law by using the rules of fiqh al-masyaqqah tajlibu al-taysīr as a framework for analysis. The method used is normative juridical law research with a literature approach, through the analysis of primary and secondary sources in the form of the Qur'an, hadith, fiqh books, Compilation of Islamic Law, and laws and regulations. The results of the study show that nikah siri can be considered valid in fiqh if it meets the principles and conditions, but it does not have legal force in the country's legal system, so it has implications for weak legal protection, especially for women and children. Meanwhile, an online marriage contract can be considered valid according to some scholars as long as it fulfills the substantive elements of the contract, although it still faces challenges in the aspect of formal legality. The discussion shows that the application of the rules of al-masyaqqah tajlibu al-taysīr reflects the flexibility of Islamic law in responding to social dynamics without neglecting maqāṣid al-syarī'ah and legal certainty. Therefore, it is necessary to harmonize adaptive regulations and strengthen marriage registration to ensure legal certainty and protection, while affirming that formal legality is an essential aspect in contemporary marriage practices.